ADVERSE AGRICULTURAL CONSEQUENCES OF WEATHER MODIFICATION - J. Marvin Herndon (AGRIVITA, Journal of Agricultural Science, 2016)
For at least fifteen years, with ever increasing frequency and extent, weather modification and/or climate alteration investigations have been conducted without public disclosure to perfect a covert methodology for inhibiting rainfall to deliberately damage a sovereign nation’s agri-cultural economy. This research discloses methodology for inhibiting rainfall, the evidence of coal combustion fly ash utilization, the adverse consequences on agriculture, and the adverse health implications on biota, including humans. The harm to agriculture comes primarily from aluminum addition to soil, changing soil pH and changing historic weather patterns. Aluminum in a chemically mobile form, not only harms plants, but is toxic to most biota, including humans. The micron and submicron particulates are used for weather modification contain heavy metals and radioactive elements which pose potentially grave human health threats including, but not limited to, cardiovascular disease, diabetes, respiratory diseases and reduced male fertility. Understanding that methodology and its adverse consequences by the agricultural community is crucial to identify and stop covert operations aimed at damaging the agricultural economy of a sovereign nation.